Charge-ordering induces magnetic axes rotation in organic materials (TMTTF)₂X (with X = SbF₆, AsF₆, and PF₆) - Dutoit, C.-E.; Bertaina, S.; Orio, M.; Dressel, M.; Stepanov, A. (Физика низких температур, 2015)
We have performed a comprehensive EPR investigation of the quasi-one-dimensional organic systems (TMTTF)₂X with centrosymmetrical anions X (X = SbF₆, AsF₆, and PF₆). We observe a strong rotation of g-factor principal axes when the temperature decreases below charge-ordering temperature TCO. The possible origin of this rotation is analyzed on the basis of quantum chemical calculations performed using density functional theory method. A good agreement between theory and experiment is found.